Impact of Problem Based Learning-Blended Learning on Students’ Creativity and Learning Interest - Irwandi; Yuli Hartati; Tomi Hidayat; Apriza Fitriani (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to find out whether there is an increase in creative thinking and interest in learning Biology using the Problem Based Learning model based on Blended Learning (PBL-BL). This type of research is Quasi Experimental with a None Equivalent (Pretest and Posttest) Control Group Design. The population was 116 students in class XI MIPA SMA Negeri 4 Bengkulu City, three sample classes, two experimental classes and one control class. The data collection method uses the Torrance creative thinking test and questionnaires to measure students' interest in learning Biology. Data were analyzed using the One Way Anova test. The results of the research show that there is an increase in students' creative thinking power and interest in learning by implementing the Problem Based Learning model based on Blended Learning (PBL-BL) in Biology learning.